The Evolution of Library Instruction Delivery in the Chemistry Curriculum Informed by Mixed Assessment Methods. - Meris A. Mandernach; Yasmeen Shorish; Barbara A. Reisner (Issues in Science and Technology Librarianship)
As information continues to evolve over time, the information literacy expectations for chemistry students also change. This article examines transformations to an undergraduate chemistry course that focuses on chemical literature and information literacy and is co-taught by a chemistry professor and a chemistry librarian. This article also describes results from assessment of both content knowledge and student perception, and discusses how the assessment was used to inform changes to the course. This type of student assessment and evaluation has not previously been examined in the delivery of required undergraduate chemistry information courses. Since this course has used in-person, online, and blended delivery methods, the article describes what students can learn from online modules, and where they need more intensive classroom instruction. [ABSTRACT FROM AUTHOR]